Involvement of peripheral artemin signaling in tongue pain: possible mechanism in burning mouth syndrome. Issue 12 (December 2015) - Shinoda, Masamichi; Takeda, Mamoru; Honda, Kuniya; Maruno, Mitsuru; Katagiri, Ayano; Satoh-Kuriwada, Shizuko; Shoji, Noriaki; Tsuchiya, Masahiro; Iwata, Koichi
Abstract : Abstract: Burning mouth syndrome is characterized by altered sensory qualities, namely tongue pain hypersensitivity. We found that the mRNA expression of Artemin (Artn) in the tongue mucosa of patients with burning mouth syndrome was significantly higher than that of control subjects, and we developed a mouse model of burning mouth syndrome by application of 2, 4, 6-trinitrobenzene sulfonic acid (TNBS) diluted with 50% ethanol to the dorsum of the tongue. TNBS treatment to the tongue induced persistent, week-long, noninflammatory tongue pain and a significant increase in Artn expression in the tongue mucosa and marked tongue heat hyperalgesia. Following TNBS treatment, the successive administration of the transient receptor potential vanilloid 1 (TRPV1) antagonist SB366791 or neutralizing anti-Artn antibody completely inhibited the heat hyperalgesia. The number of glial cell line–derived neurotrophic factor family receptor α3 (GFRα3)-positive and TRPV1-positive trigeminal ganglion (TG) neurons innervating the tongue significantly increased following TNBS treatment and was significantly reduced by successive administration of neutralizing anti-Artn antibody. The capsaicin-induced current in TG neurons innervating the tongue was enhanced following TNBS treatment and was inhibited by local administration of neutralizing anti-Artn antibody to the tongue. These results suggest that the overexpression of Artn in the TNBS-treated tongue increases the membrane excitability of TG neurons innervating the tongue by increasing TRPV1 sensitivity, which causes heat hyperalgesia. This model may be useful for the study of tongue pain hypersensitivity associated with burning mouth syndrome. Abstract : The upregulation of TRPV1 in trigeminal ganglion neurons innervating tongue via GFRα3-mediated signaling contributes heat hypersensitivity observed in a mouse model of burning mouth syndrome.